Beyond the task trainer: Enhancing empathy and competence through hybrid simulation. - Ciccone, Jennifer; Hairfield, Christopher; Engelhardt, Mathew (Clinical Simulation in Nursing, 2026)
• Hybrid simulation integrated a standardized patient with a wearable catheterization trainer. • Students reported higher engagement and confidence than with mannequin-only simulation. • Hybrid simulation increased perceived realism and therapeutic communication confidence. • SP feedback enhanced learners' therapeutic communication and engagement. • Integrating SPs in skills labs bridged technical and interpersonal competence. Urinary catheterization is a sensitive clinical skill that requires not only technical proficiency, but also therapeutic communication to preserve patient dignity and trust. Traditional task-trainer simulations provide opportunities to practice psychomotor skills but lack the emotional realism and interpersonal engagement needed to prepare students for authentic patient care. The project was conducted with 67 second-semester students enrolled in an Accelerated Bachelor of Science in Nursing (ABSN) program and concurrently taking a foundational medical-surgical nursing course. This quality improvement project implemented a hybrid simulation experience that combined a wearable urinary catheterization task trainer with a standardized patient (SP). The intervention aimed to evaluate students' satisfaction with the learning experience, their preferences for SP-based versus mannequin-based training, and their self-perceived communication competence during the procedure. Data were collected through post-simulation surveys and de-identified for analysis. Students reported significantly higher satisfaction and perceived realism with the hybrid simulation compared to mannequin-only training. They highlighted the value of authentic patient interaction, noting that the SP's verbal and nonverbal feedback enhanced their confidence in therapeutic communication while maintaining procedural accuracy. The majority expressed a preference for hybrid simulation in future skills training. Hybrid simulation offers a valuable approach to bridging the gap between procedural competence and compassionate care. By integrating SPs into technical training, nursing programs can better prepare students for sensitive clinical encounters, ensuring graduates are equipped with both technical expertise and interpersonal skills essential to professional practice.